2016
DOI: 10.7863/ultra.15.11050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoking on Elastographic Strain Ratio Measurements of Patellar and Achilles Tendons

Abstract: Thickness and strain ratio measurements of patellar and Achilles tendons were reduced (thinner and harder tendons) in smokers. Clinical implications of these morphologic and elastographic changes should be investigated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
(61 reference statements)
1
23
1
Order By: Relevance
“…Nicotine's vasoconstrictive properties are well known and our ultrasound data confirms that nicotine hinders blood flow in tendons. Furthermore, our biomechanical data reveal that nicotine leads to decreased cross sectional area of the injured tendon (i.e., less scar formation at the injury site), in concordance with previous literature . Data suggest that nicotine results in less hypertrophic scar and keloid formation, as well as decreased proliferation of myofibroblasts in post‐surgical scars .…”
Section: Discussionsupporting
confidence: 91%
“…Nicotine's vasoconstrictive properties are well known and our ultrasound data confirms that nicotine hinders blood flow in tendons. Furthermore, our biomechanical data reveal that nicotine leads to decreased cross sectional area of the injured tendon (i.e., less scar formation at the injury site), in concordance with previous literature . Data suggest that nicotine results in less hypertrophic scar and keloid formation, as well as decreased proliferation of myofibroblasts in post‐surgical scars .…”
Section: Discussionsupporting
confidence: 91%
“…9 Furthermore, in a clinical study that analyzed the Achilles tendon with ultrasonography, it was found that smoking was associated with a thinner tendon and increased strain ratio. 1 In our study, we did not detect a difference in AT or SS CSA, which may explain why we did not observe changes in modulus that was observed in these previous studies. Furthermore, our rats received a dose of nicotine equivalent to the average American smoker (14 cigarettes per day) where the previous studies had nicotine doses for heavy smoker (>20 cigarettes per day).…”
Section: Discussioncontrasting
confidence: 61%
“…The retrospective cohort study in patients with calcified calcific tendinitis of the rotator cuff found smoking was significantly associated with a failure of needle aspiration of calcific deposits (n ACD) (adjusted OR = 1.7, 95% CI: 1.0-2.7, P = 0.04) [ 246 ]. One case-control study reported smokers had significantly thinner patellar and Achilles tendons in the proximal, middle, and distal thirds region of the tendons and significant lower strain ratio measurements in the same regions (P < 0.05); pack-years were inversely related to patellar tendon thickness (P < 0.05) [ 241 ]. One cross-sectional study reported smokers had significant improvement in finger range of motion over nonsmokers after tendon grafting [ 243 ].…”
Section: Resultsmentioning
confidence: 99%